Przyczynek do zagadnieniaprzyczynowości zaniechania - Patryas, Wojciech (Wydział Prawa i Administracji UAM, 1992)
The basis of the article is the conviction that offences committed through omission are a separate category of offences. Their separate character manifests itself through their lack of causal character. It can be seen especially in case of so-called non-proper offences committed through omission; it makes it necessary to amend some provisions of the Criminal Code.
Contribution to the problem of causality of forbearance